Occurrence of mental health symptoms and disorders in current and former elite athletes: a systematic review and meta-analysis - Gouttebarge, Vincent; Castaldelli-Maia, João Mauricio; Gorczynski, Paul; Hainline, Brian; Hitchcock, Mary E; Kerkhoffs, Gino M; Rice, Simon M; Reardon, Claudia L (British journal of sports medicine, 2019)
ObjectivesTo present an overview of the existing epidemiological evidence regarding the occurrence of mental health symptoms and disorders among current and former elite athletes.DesignSystematic review and meta-analysis.Data sourcesFive electronic databases were searched from inception to November 2018: PubMed (MEDLINE), SportDiscus via EBSCO, PSycINFO via ProQuest, Scopus and Cochrane.Eligibility criteria for selecting studiesWe included original quantitative studies that were written in English, were conducted exclusively among current or former elite athletes, and presented incidence or prevalence rates of symptoms of mental disorders.ResultsTwenty-two relevant original studies about mental health symptoms and disorders among current elite athletes were included: they presented data especially on symptoms of distress, sleep disturbance, anxiety/depression and alcohol misuse. Meta-analyses comprising 2895 to 5555 current elite athletes showed that the prevalence of mental health symptoms and disorders ranged from 19% for alcohol misuse to 34% for anxiety/depression. Fifteen relevant original studies about mental health symptoms and disorders among former elite athletes were included: they similarly presented data especially about symptoms of distress, sleep disturbance, anxiety/depression and alcohol misuse. Meta-analyses comprising 1579 to 1686 former elite athletes showed that the prevalence of mental health symptoms and disorders ranged from 16% for distress to 26% for anxiety/depression.ConclusionsOur meta-analyses showed that the prevalence of mental health symptoms and disorders ranged from 19% for alcohol misuse to 34% for anxiety/depression for current elite athletes, and from 16% for distress to 26% for anxiety/depression for former elite athletes.